Contribuição à enfermagem gerontológica: um estudo exploratório - Vale, Rosalina Rosana do (2013)
The aging process underway in Brazilian society coupled with increased life expectancy has the effect of the high number of elderly people over 60 years. Given this, it is relevant to new reflections and analyzes of health promotion and disease prevention in the elderly population aging situation. This paper is a literature review conducted in academic articles and books that deal with the theme of Gerontological Nursing. In this sense, I tried searching dissertations conducted by nurses in the Post- Graduate in Gerontology, thinking that contribute to the interfaces between the Nursing and Gerontology, reflecting on the contributions of Gerontological Nursing to think about the present and the challenges for nursing professionals regarding the expansion of the aging population and specific care for older people